STUDENTS’ DIFFICULTIES IN WRITING DEFINITION PARAGRAPH AT THE THIRD SEMESTER STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF STKIP NIAS SELATAN - Wau, Christiana Surya Wati (Universitas Nias Raya, 2022)
Writing is one of the main issues encounter by college students who learn English as foreign language. The third semester students of STKIP Nias Selatan encounter this problem. The students were unable to deliver their ideas into structural paragraph particularly when they were asked to write a definition paragraph. This study aims to reveal how are the difficulties faced by the students and what factors caused them. The research was designed in qualitative research design. The researcher collected the data from the students’ papers and interview session. Initially, the researcher collected the students’ paper and then analyzed them. Furthermore, the researcher conducted an interview to acquire what factors caused the difficulties. Based on the data analysis, the researcher found that the students encountered difficulties in writing definition paragraph. They found difficulties in the five aspects of writing. The factors that caused difficulties were: the ignorance of a well-organized paragraph, unconsciousness of non existence of a part of paragraph definition, not good at grammar, lack of vocabulary, unawareness of indentation usage, unawareness of the use of proper spelling, self ignorance of proper capitalization, and the inconducive environment and less time. Therefore, it is recommended to English lecturer to more emphasize in teaching grammar, vocabulary, the rules of writing definition paragraph in particular so that the students would be able to overcome the difficulties in producing a definition paragraph further, as well as for other genres of writing in general.